The small economies of Latin America and the Caribbean - Hubert Escaith (CEPAL Review, 2001)
Population, natural resources and domestic market size have been the traditional components of the equation determining the wealth of nations, according to classical economists. The new lines of research opened up by endogenous growth theories and the results of comparative statistical studies into the factors determining this growth have reawakened interest in the relationships between scale effects, market size and the role of international trade in the economic growth of small economies. At a time of ever-increasing globalization, these economies are being confronted with a number of challenges and opportunities in relation to which their small economic size is generally regarded as a disadvantage. Diseconomies of scale increase their production costs, while their relatively undiversified exports mean they are extremely vulnerable to shocks of external origin. All these factors weigh all the more heavily in that trade has become one of the key factors in economic development, as is demonstrated by the sharp increase in imports and exports as a share of GDP since the second half of the 1980s. The central role played by intraregional trade or the North American market as non-traditional export engines is heightening the importance of price competitiveness, and thus of subsidy or tax exemption programmes to ensure an outlet to these markets. For those small developing countries in the region that suffer relative disadvantages, success would therefore seem to depend on the preferential terms under which they do business with their main developed-world trading partners, namely North America and, for members of the ACP group (the developing countries of Africa, the Caribbean and the Pacific), the European Union. Again, excessive specialization to serve a large regional market (Brazil or the United States) entails risks that merit consideration.